Public administration: State apparatus leadership in the present era - Romi Saputra (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: Achieving leadership success in the modern era takes time and effort. It is a public administration challenge to find the appropriate response for leaders in a situation where it is hoped that they will be able to make many changes by adopting new paradigms of publicadministration and management. Methodology: This study employs a qualitative, descriptive methodology. Information was gathered from reading materials and relevant scholarly articles. Findings: According to the study’s results, leaders open to change and lifelong learning are best positioned to meet the challenges of public administration under the new leadership paradigm. There is a need for leaders who can transform organizations to meet the challenges of modern public administration. Leaders fearless in adapting to new circumstances are essential in today’s world, where rapid, dynamic changes are the norm so that institutions like the state stay caught up. Implications/Novel Contribution: There has been a shift toward a new paradigm in leadership in recent years, as it has become clear that the old ways of doing things won’t cut it in the era’s world. This study provides an overarching look at the types of leadership required to keep a team on track during the transition while being flexible enough to meet immediate needs.